Synthesis of a novel carboxymethyl chitosan-silver - ginger nanocomposite, characterization, and antimicrobial efficacy - Manal A. El-Sheikh (Carbohydrate Polymer Technologies and Applications)
Over 70 % of bacterial infections are resistant to one or more of the antibiotics are generally used to eliminate infections. Silver nanoparticles (AgNPs), ginger oil, and carboxymethyl chitosan (CMC) are among the materials and the green natural products that possess antimicrobial properties. In this study, combinations of the medicinal properties of CMC, AgNPs, and ginger oil were put together in one product via the synthesis of CMC-Ag-Ginger-nanocomposite. To increase the miscibility of ginger oil -used in the synthesis-, different surfactants were applied to the synthesis aqueous medium. Thus, the nanocomposite synthesized in such way assumed a new method. In addition, the nanocomposite produced using ginger oil, silver nitrate, CMC, and surfactants assumed a new nanocomposite synthesized for the first time in this research work. The Optimum reaction conditions that brought the highest AgNPs absorbance and the formation of CMC-Ag-Ginger-nanocomposite were studied. For better miscibility of ginger oil, glycerin, Tween 80, or Egyptol were applied to the synthesis aqueous medium. AgNPs obtained were evaluated by the absorbance of the nanocomposite colloidal solution. Optimum conditions: 0.5 % (w/v) Egyptol, 0.01M AgNO3, 0.5 % (w/v) ginger oil, 3 % (w/v) carboxymethyl chitosan, 95°C for 3h. A decrease in N % of CMC-Ag-G-nanocomposite (3.04 %) compared with N % of CMC (4.03 %) confirmed the formation of the nanocomposite. TEM showed spherical shape AgNPs with size range of 8–35 nm, whereas highest count % was 12–25 nm. SAED of AgNPs exhibited ring patterns with bright spots displaying polycrystallinity which agreed with XRD. SEM of CMC-Ag-G-nanocomposite showed porous structure and well distribution of AgNPs within CMC polymer. TGA showed that CMC-Ag-G-nanocomposite is more thermally stable than CMC. CMC-Ag-G-nanocomposite showed higher antibacterial efficacy against S. Aureus and E. coli and higher antimicrobial efficacy against Aspergillus Niger and Candida albicans compared to CMC. These findings render the newly prepared nanocomposite suitable for medical and other applications.